2020
DOI: 10.1038/s41467-020-14683-5
|View full text |Cite
|
Sign up to set email alerts
|

Mahan excitons in room-temperature methylammonium lead bromide perovskites

Abstract: In a seminal paper, Mahan predicted that excitonic bound states can still exist in a semiconductor at electron-hole densities above the insulator-to-metal Mott transition. However, no clear evidence for this exotic quasiparticle, dubbed Mahan exciton, exists to date at room temperature. In this work, we combine ultrafast broadband optical spectroscopy and advanced many-body calculations to reveal that organic-inorganic lead-bromide perovskites host Mahan excitons at room temperature. Persistence of the Wannier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 65 publications
7
55
3
Order By: Relevance
“…We believe that the photoexcited carrier density in our experiment lies below the actual value of n M . Persistence of excitonic correlations above n M have been recently demonstrated in several semiconductors [7,8,10] and the emergence of Mahan excitons has been invoked [10]. However, in such a scenario, the Wannier exciton feature would be accompanied by the enhancement of the continuum absorption, which is instead absent in our data.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…We believe that the photoexcited carrier density in our experiment lies below the actual value of n M . Persistence of excitonic correlations above n M have been recently demonstrated in several semiconductors [7,8,10] and the emergence of Mahan excitons has been invoked [10]. However, in such a scenario, the Wannier exciton feature would be accompanied by the enhancement of the continuum absorption, which is instead absent in our data.…”
mentioning
confidence: 50%
“…More refined theoretical analysis [4,6] and extensive experimental work [7][8][9][10][11][12][13] have instead revealed a rich phase diagram of exotic states persisting above n M . Notable examples include robust excitonic and biexcitonic correlations [7][8][9], emergent Mahan excitons [10], anomalous metallic states [11], e-h droplets [12,13], and possible Bose condensates of photoexcited e-h Cooper pairs [4]. Therefore, the identification of n M in semiconductors acquires a crucial importance for discovering hitherto unobserved phenonena and clarifying how excitons react to the large carrier densities present in many optoelectronic devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29 Recently, it was found that excitons are surprisingly persistent in bulk CH3NH3PbBr3 perovskite above the Mott density, which is attributed to Mahan excitons. 30 It is therefore unclear whether an electron-hole plasma is stabilized at densities in the range of 10 18 -10 19 cm -3 for 2D perovskites. This motivates an analysis of the THz absorption spectra at different time delays to discern the evolution of free carriers into excitons.…”
Section: Resultsmentioning
confidence: 99%
“…If we were in a regime where the Mott transition was starting to play a role, then Eb should decrease with fluence as the screening becomes stronger. 30 This would translate into a blueshift of the emission peak since the excitons are less stabilized. However, we do not observe any blueshift of the peak with fluence.…”
Section: Methodsmentioning
confidence: 99%